Industrial training report: University of Malaya Library / Nur Hafawati Ibrahim - Ibrahim, Nur Hafawati (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Industrial training is a key component of a student's education. Industrial training that is well-planned, well-executed, and well-evaluated can go a long way toward developing a professional attitude. It fosters an understanding of the industrial approach to problem solving, which is based on a thorough understanding of the organization's processes and modes of operation. The goal and motivation of this industrial training is to gain discipline, skills, teamwork, and technical knowledge in a proper training environment, which will aid me in developing a responsiveness to the self-disciplinary nature of problems in information and communication technology as a student in the field of information technology. Because the library profession is specialised and technical in nature, industrial training for library science students must include both theory and practical skills. With the recent debate over the relevance of libraries in the face of emerging web technologies, this is becoming increasingly relevant. The industrial training is based in part on the internship model, in which student receive one to five months of training.